Performance modelling of fuel cell systems through Petri nets - Fecarotti, Claudia; Andrews, John (2016)
This paper introduces a model based on the Petri net method for the performance evaluation of fuel cell systems during operation. The model simulates the operation of the fuel cell stack and its supporting systems by taking into account the causal relationships between the operation of the balance of plant and the fuel cell stack performance. Failures of the supporting system affect the operating parameters such as the stack temperature and humidity, the reactants’ flow and pressure, and, in turn, the stack performance in terms of output voltage. Voltage degradation rates are needed in order to evaluate the system lifetime. The voltage degradation is related to the important operating parameters by means of empirical relationships. In order to demonstrate the capability of the model, numerical simulations are performed using data for voltage degradation rates collected from the literature. The voltage decay rate is modelled as a random variable within the aforementioned ranges. Time to failure and time to repair of components are generated from stochastic distributions. The use of a stochastic approach allows taking into account data uncertainty and variability. The modelling process produces distributions of the output parameters rather than point estimates delivered by alternative methods. This enables an appreciation of the best and worst possible output lifetime as well as the expected system performance. The model can be used to support the design, operation and maintenance of fuel cell systems.